Study of Food Supplements: Background, Present and Future - Ibrahim Adnan Saraçoglu; Eda Büker (Highlights on Medicine and Medical Science Vol. 3, 2021)
The opinions of why the need for food supplements has changed throughout time are included in this study. In addition, the methods for producing dietary supplements were examined, as well as the advantages and disadvantages of each method. Food supplements and their role in natural nutrition, as well as their impact on human health, should be studied holistically rather than isolated from natural sources. Thousands of different chemical additives, microbial and biotechnological applications, and other technological processes turn a natural product into a malady. Many faults of research and development (R&D) project findings of dietary supplements might become more clearly known when studies are conducted with a holistic view.